5(a+2)-3(a-1)=3

Simple and best practice solution for 5(a+2)-3(a-1)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(a+2)-3(a-1)=3 equation:



5(a+2)-3(a-1)=3
We move all terms to the left:
5(a+2)-3(a-1)-(3)=0
We multiply parentheses
5a-3a+10+3-3=0
We add all the numbers together, and all the variables
2a+10=0
We move all terms containing a to the left, all other terms to the right
2a=-10
a=-10/2
a=-5

You can always share this solution

See similar equations:

| X+8/x-2=1+4x/x-2 | | -7(a-4)=14 | | 7(x-10)=5x | | a?(?7a?3)=0 | | z^z^-8z=0 | | 3d-4d+8d=28 | | y-2/3=6 | | 2x+x+x+x=470 | | 4x-4=-5(7x-6)+83 | | (32/x)+6x=90 | | 32/x+6x=90 | | (-17-3r/2)=-19 | | (3-x)(4-x)-2=0 | | 1x^2-7x+2=-8 | | x4-15x2=16 | | f/4+75=158 | | 5x+13+4x+12=11x+3 | | (3x+5)/4-(2x-1)/3=2 | | 5x+13+4x+12+11x+3=180 | | 13f-72=760 | | 7f+49=434 | | 6m+21/2=33/2 | | (x+10)/2+3=2 | | x+10/2+3=2 | | 6x^2-9x-56.5=0 | | 33/2x-5-3=1/4 | | 5x+8-7x=15-17x+15x-7 | | 4(3x+4)=-4x+5 | | 6(4x-3)=9x+2 | | 5y-7+y+25=8y+20-4y | | 7c+13c=160 | | 5?(x-3)+8x=6x-5+x |

Equations solver categories